Peningkatan Kesembuhan Pasien melalui Pastoral Orang Sakit di Rumah Sakit Umum Santo Antonius Pontianak - Meliyanto, Adi Ria Singir (Borneo Review, 2022)
This research is based on the author's concern about the lack of Pastoral services, especially for the sick. Sick people I mean are patients who are treated at the general hospital of Santo Antonius Pontianak, which is the locus of this research. As far as the researchers observed, they only get physical attention but spiritual needs are often ignored by the hospital. In solving the problem, the author uses a descriptive-qualitative form of research. From the results of data processing, it can be concluded that Pastoral for the Sick is carried out by employees appointed by the hospital, Pastors, and Sisters. Approximately three hours for each room, each patient is visited for 2-10 minutes, 2-3 times a week and the most often given to patients is the sacrament service (Communion and extreme unction) by the Pastor or Sister (nun), Patient Catholics are given priority to receive Pastoral Care for the Sick. While non-Catholic patients are given if there is a request from the family or the patient himself. The effects of Pastoral Care on the Sick in non-Catholic patients are not very visible. However, the patients who are Catholics think they feel very happy, feel comforted, feel strengthened, have peace, feel perfect, and are increasingly aware of God's presence. Patients like there is inner peace, this can be seen in the depression and anxiety of patients who are reduced. Keywords: Service, Pastoral, Sick People. This research is based on the author's concern about the lack of Pastoral services, especially for the sick. Sick people I mean are patients who are treated at the general hospital of Santo Antonius Pontianak, which is the locus of this research. As far as the researchers observed, they only get physical attention but spiritual needs are often ignored by the hospital. In solving the problem, the author uses a descriptive-qualitative form of research. From the results of data processing, it can be concluded that Pastoral for the Sick is carried out by employees appointed by the hospital, Pastors, and Sisters. Approximately three hours for each room, each patient is visited for 2-10 minutes, 2-3 times a week and the most often given to patients is the sacrament service (Communion and extreme unction) by the Pastor or Sister (nun), Patient Catholics are given priority to receive Pastoral Care for the Sick. While non-Catholic patients are given if there is a request from the family or the patient himself. The effects of Pastoral Care on the Sick in non-Catholic patients are not very visible. However, the patients who are Catholics think they feel very happy, feel comforted, feel strengthened, have peace, feel perfect, and are increasingly aware of God's presence. Patients like there is inner peace, this can be seen in the depression and anxiety of patients who are reduced.